2021
DOI: 10.3390/ijerph182111299
|View full text |Cite
|
Sign up to set email alerts
|

Are Resistance Training-Induced BDNF in Hemodialysis Patients Associated with Depressive Symptoms, Quality of Life, Antioxidant Capacity, and Muscle Strength? An Insight for the Muscle–Brain–Renal Axis

Abstract: Background: Hemodialysis patients are suffering from depressive symptoms. Brain-derived neurotrophic factor (BDNF) levels are negatively associated with depressive symptoms and decrease during a single hemodialysis session. Resistance training (RT) might be an additional non-pharmacological tool to increase BDNF and promote mental health. Methods: Two randomized groups of hemodialysis patients: control (CTL, n = 76/F36; 66.33 ± 3.88 years) and RT (n = 81/F35; 67.27 ± 3.24 years). RT completed six months of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…BDNF is involved in the regulation of synaptic function and in the maintenance of the neuromuscular system as well as in muscle development and metabolism [ 28 ]. Deus et al [ 29 ] showed that 6 months of resistance training just before HD sessions improved handgrip strength in line with increased BDNF. Serum BDNF levels were also positively associated with handgrip strength, role-emotional, and emotional well-being scales and negatively associated with the Beck depression inventory score [ 29 ].…”
Section: Nutritional Assessment Methods For Dialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF is involved in the regulation of synaptic function and in the maintenance of the neuromuscular system as well as in muscle development and metabolism [ 28 ]. Deus et al [ 29 ] showed that 6 months of resistance training just before HD sessions improved handgrip strength in line with increased BDNF. Serum BDNF levels were also positively associated with handgrip strength, role-emotional, and emotional well-being scales and negatively associated with the Beck depression inventory score [ 29 ].…”
Section: Nutritional Assessment Methods For Dialysis Patientsmentioning
confidence: 99%
“…Deus et al [ 29 ] showed that 6 months of resistance training just before HD sessions improved handgrip strength in line with increased BDNF. Serum BDNF levels were also positively associated with handgrip strength, role-emotional, and emotional well-being scales and negatively associated with the Beck depression inventory score [ 29 ]. Miyazaki et al [ 30 ] evaluated the relationship between BDNF and sarcopenia and frailty in regular patients on HD.…”
Section: Nutritional Assessment Methods For Dialysis Patientsmentioning
confidence: 99%
“…Two of these studies also showed increased levels of exercise-induced NGF (Jafarzadeh et al, 2021;Rahmati et al, 2022) Frontiers in Neuroscience 04 frontiersin.org the brain of resistance-trained animals (Pena et al, 2020). Human studies investigating the effects of RE in the elderly population have indicated that programs with 12 weeks to 6 months of exercise increase peripheral BDNF levels (Roh et al, 2020;Deus et al, 2021;Castaño et al, 2022). Furthermore, higher BDNF levels were observed after a single RE session (Arazi et al, 2021).…”
Section: Influence Of Re On Neurotrophic Factors In Admentioning
confidence: 97%
“…A total of 1066 studies were found (Supplementary Fig. 1), and 179 potentially includable studies were identified through the title and abstract, of which 30 RCTs [17,[23][24][25] met the eligibility criteria and were included in the systematic review; of these, 27 were included in the meta-analysis [17,23,[30][31][32][33][34][35][36][37][38][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] (3 were excluded because no data were available).…”
Section: Study Selectionmentioning
confidence: 99%
“…The RCTs were conducted in the following continents: Oceania [39], Asia [17,32,33,42,44,48,50], Europe [24,31,41,43,45,46,52] and America [23,25,30,[34][35][36][37][38]40,47,49,[53][54][55]]. In addition, 22 studies were performed in a healthy population, described as individuals without specific health disorders or pathologies [23,24,[30][31][32][34][35][36][37][38]40,[42][43][44][45][46][47][49][50][51]53,…”
Section: Study and Intervention Characteristicsmentioning
confidence: 99%